929. Characteristics Associated with Pain in Older People Living with HIV. (31st December 2020) - Karris, Maile; Mazonson, Peter; Loo, Theoren; Berko, Jeff; Spinelli, Frank; Zolopa, Andrew
Abstract: Background: Pain impacts up to 55% of people living with HIV (PLWH) and negatively impacts function. To date, limited data exist regarding factors that contribute to pain in older PLWH. Methods: Data were utilized from the Aging with Dignity, Health, Optimism and Community (ADHOC) cohort, an observational study of older PLWH from ten clinics across the U.S. that collects patient-reported outcomes (PROs) on socioeconomic, psychosocial, and health factors. To measure pain, ADHOC participants were asked whether they had been diagnosed with back pain, hip pain, joint pain, or muscle pain, and were also instructed to report chronic pain conditions that were not listed. Bivariate analyses were performed to determine the associations between pain and PROs. Results: Of 1, 051 participants, 66% reported at least one type of pain. Factors associated with pain included multimorbidity, low income, anxiety, loneliness, depression, tobacco use, and older age (Table 1). Factors negatively associated with pain included employment, higher cognitive function, higher quality of life, greater resilience, higher social well-being, and alcohol use. Table 1. Characteristics associated with pain among older people living with HIV. Pairwise correlations are reported above using correlation coefficient r. Conclusion: Improving pain management is currently a priority in the US healthcare system. Some factors identified in this study, including systemic issues such as socioeconomic status and employment, are not easily modifiable. Other factors, such as anxiety, depression, and smoking, are modifiable and therefore represent targets for interventions focused on improving pain and its sequelae in older PLWH. Disclosures: Maile Karris, MD, Gilead Sciences (Grant/Research Support)Viiv Healthcare (Grant/Research Support) Peter Mazonson, MD, MBA, ViiV Healthcare (Grant/Research Support) Theoren Loo, MS, BS, ViiV Healthcare (Grant/Research Support) Jeff Berko, MPH, BS, ViiV Healthcare (Grant/Research Support) Frank Spinelli, MD, ViiV Healthcare (Employee) Andrew Zolopa, MD, ViiV Healthcare (Employee)